Inmunolocalizacion hepática de CYP P450 en un experimento de toxicidad subaguda por Clorpirifos 0,0-dietil 0-(3, 5, 6-tricloro-2-piridil fosforotioato) en machos juveniles de tilapia (Oreochromis spp) (2013)
ABSTRACT: In Colombia the diagnostic techniques for implementing immunohistochemical biomarkers to fulfill biomonitoring of environmental contamination are limited. Objective: To implement an immunohistochemical technique to immunolocate CYP 1A in the tissue of fish, performing a subacute exposition experiment of Clofopirifos in the liver of young male tilapia. Methods: the sublethal dosage was carried out in semi-static state, with a daily refill of 50% of the water volume, maintaining the corresponding concentration in each group through the addition of half of the dosage until the 28th day. The Cloropirifos concentrations for the exposition were 4, 8, and 12 μg/L in the treated group and 0.0 μg/L in the control group. Samples were taken for histopathological and immunohistochemical study. Results: A significant difference (p<0.05) for some liver lesions, confirming that it is an organ affected by low dosages of Cloropirifos. It verified that the induction of CYP 1A in hepatocyte, endothelium and biliary cells equally in exposed animals and those that weren’t exposed. From a multidimensional perspective, no statistical difference was found between the treatments for the variables under study. Conclusion: this study implemented and normalized an immunohistochemical technique for the tissue immunolocation of CYP 1A that could be used in future investigations to fulfill biomonitoring of contamination in Colombia’s hydrographic basins.